Mn-doped nanocrystals in light-emitting diodes: energy-transfer to obtain electroluminescence from quantum dots - Rath, Arup Kumar; Bhaumik, Saikat; Pal, Amlan J. (Applied Physics Letters, 2010)
We fabricatelight-emitting diodes(LEDs) based on Mn-doped ZnSnanocrystals along with hole-transporting bis(3-methylphenyl)--diphenyl-benzidine (TPD). With Mn-doping, ZnSnanostructures exhibit a strong photoluminescence. The LEDs exhibit electroluminescence(EL) from Mn-doped ZnSquantum dots and TPD. In order to open up channels for energy-transfer from TPD to quantum dots and to achieve EL from only the nanoparticles, we grow core-shell nanoparticles with Mn-doped ZnS in the core and CdS as the shell layer. Excitons formed in TPD can now transfer their energy directly to the shell-layer to yield EL from only the nanoparticles.

Perspective on perovskite solar cells - Bhaumik, Saikat; Saha, Sudip K.; Rath, Arup K. (New Research Directions in Solar Energy Technologies, 2021)